PEI-CQDs composite material, gel and preparation methods of PEI-CQDs composite material and gel

The PEI-CQDs composite material prepared by reacting carbon quantum dots with polyethyleneimine solves the problem that low molecular weight PEI is difficult to apply to water plugging agents, and the effect of improving PEI molecular weight and branching degree, shortening gel time and improving performance is achieved.

CN119613954AActive Publication Date: 2025-03-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311174750.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-14
Estimated Expiration
2043-09-12

AI Technical Summary

Technical Problem

Low molecular weight polyethyleneimine (PEI) is difficult to apply to the production of water plugging agents, and the prior art cannot effectively improve the molecular weight and branching degree of PEI.

Method used

By reacting carbon quantum dots (CQDs) with polyethyleneimine (PEI) in the presence of an additive, a PEI-CQDs composite material was prepared, and the carbon quantum dots were covalently modified to increase the molecular weight and branching degree of PEI.

Benefits of technology

The application of low molecular weight PEI in gel preparation is achieved, which shortens the gel time and improves the performance of the water plugging agent of the gel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613954A_ABST
    Figure CN119613954A_ABST
Patent Text Reader

Abstract

The invention relates to the field of gel, and discloses a PEI-CQDs composite material, gel and preparation methods of the PEI-CQDs composite material and the gel, and the preparation method of the PEI-CQDs composite material comprises the following steps: (1) electrolyzing graphite in water to obtain carbon quantum dots; and (2) carrying out a reaction on the carbon quantum dots and polyethyleneimine in the presence of an optional auxiliary agent to obtain the PEI-CQDs composite material. The PEI-CQDs composite material can be applied to the preparation process of gel, so that PEI with low molecular weight can also be used for preparing gel, and the gelation time can be shortened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of gel, and in particular to a method for preparing a PEI-CQDs composite material, a PEI-CQDs composite material prepared by the method, application of the PEI-CQDs composite material in preparing gel, a method for preparing gel and a gel. Background Art

[0002] As a new type of carbon nanomaterial, carbon quantum dots (CQDs) not only have small particle size, but also have large specific surface area, a large number of active sites on the surface, good water solubility and easy functionalization. The abundant oxygen-containing functional groups such as carboxyl, hydroxyl, and epoxy groups on the surface make them negatively charged when hydrolyzed in water.

[0003] Polyethyleneimine (PEI) is a water-soluble high molecular polymer. As a typical gel-type water plugging agent, PEI gel has the advantages of low surface viscosity, easy to enter the hyperosmotic layer first, adjustable freezing time and gel strength, and low toxicity. The high molecular weight polyethyleneimine prepared by the existing technology is mainly produced by BASF and Japan Catalyst Company abroad. Only a few companies in China produce PEI. The main reason is that there are few raw material ethyleneimine production companies and the technology for preparing PEI by ethyleneimine polymerization is not up to standard. However, low molecular weight polyethyleneimine (especially PEI with a molecular weight of less than 2000g / mol) is difficult to be used in water plugging agents. Summary of the invention

[0004] The purpose of the present invention is to overcome the problem that low molecular weight PEI is difficult to be used in the production of water plugging agents, and to provide a PEI-CQDs composite material and a preparation method thereof. The PEI-CQDs composite material can be applied to the preparation process of gel, so that low molecular weight PEI can also be used to prepare gel and the gel time can be shortened.

[0005] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a PEI-CQDs composite material, the method comprising:

[0006] (1) electrolyzing graphite in water to obtain carbon quantum dots;

[0007] (2) reacting carbon quantum dots and polyethyleneimine in the presence of an optional auxiliary agent to obtain a PEI-CQDs composite material.

[0008] Preferably, in step (1), the method for preparing carbon quantum dots comprises: using graphite rods as anode and cathode, using a direct current power supply to perform electrolysis in water to obtain an electrolyte, and purifying the electrolyte to obtain carbon quantum dots.

[0009] Preferably, the voltage is 5-50V, more preferably 10-40V.

[0010] The PEI-CQDs composite material is prepared by the method provided in the second aspect of the present invention.

[0011] The third aspect of the present invention provides a PEI-CQDs composite material, wherein the PEI-CQDs composite material comprises polyethyleneimine covalently modified with carbon quantum dots;

[0012] Among them, the molar ratio of hydroxyl to carbonyl in the oxygen-containing functional groups on the surface of the carbon quantum dots is less than 1.

[0013] The fourth aspect of the present invention provides the use of the PEI-CQDs composite material as described above in preparing a gel; preferably in preparing a polyacrylamide gel.

[0014] A fifth aspect of the present invention provides a method for preparing a gel, the method comprising: contacting and reacting the PEI-CQDs composite material as described above with polyacrylamide in the presence of water to obtain a gel.

[0015] A sixth aspect of the present invention provides a gel prepared by the method described above.

[0016] In the present invention, carbon quantum dots are prepared using graphite rods as anodes and cathodes and carbon sources and water as an electrolyte solution. The experimental process is simple and environmentally friendly, and smaller CQDs are obtained. Moreover, under optimal conditions, CQDs that are more suitable for solving the technical problems of the present invention can be prepared.

[0017] The present invention grafts PEI with CQDs, which not only changes the physical and chemical properties of PEI to a certain extent and improves the functionality, but also effectively increases the molecular weight of PEI and improves the branching degree of PEI, so that low-molecular-weight PEI can also be used to prepare gel, and can shorten the gelation time and improve the performance of the prepared gel water plugging agent.

[0018] The quantum dot preparation, composite material preparation and gel reaction of the present invention all adopt a water system, and the entire preparation process does not use an organic solvent, and the prepared carbon quantum dots do not need to be separated and used directly in solution. Moreover, the preparation method is simple, the preparation process conditions are easy to control, high temperature is not required, the raw materials are easy to obtain, the entire system prepared is environmentally friendly and safe, the batches are stable, the price is low, and it has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is a transmission electron microscope photograph of CQDs prepared in Preparation Example 1 of the present invention;

[0020] Figure 2 This is a photo of the full XPS spectrum of CQDs prepared in Preparation Example 1 of the present invention;

[0021] Figure 3 is the XPS spectrum of C1s of CQDs prepared in Preparation Example 1 of the present invention;

[0022] Figure 4 It is the PEI used in Example 1 of the present invention 600 , CQDs prepared in Preparation Example 1 and PEI prepared in Example 1 600 -Infrared spectra of CQDs;

[0023] Figure 5 It is the PEI used in Example 1 of the present invention 600 , CQDs prepared in Preparation Example 1 and PEI prepared in Example 1 600 -CQDs, PEI 1800 -CQDs and PEI 10000 -Infrared spectra of CQDs;

[0024] Figure 6 For PEI 1800 GPC spectrum of

[0025] Figure 7 For PEI 1800 -GPC spectra of CQDs;

[0026] Figure 8 PAM / PEI prepared from PEI with different molecular weights (from left to right are PAM / PEI 3000 , PAM / PEI 10000 , PAM / PEI 25000 ) gel image;

[0027] Fig. 9 PAM / CQDs / PEI prepared from PEI with different molecular weights (from left to right: PAM / CQDs / PEI 3000 , PAM / CQDs / PEI 10000 , PAM / CQDs / PEI 25000 ) gel image;

[0028] Fig.10 The gel images are obtained by using different amounts of CQDs. The left image is 0.05g PAM, 2mL PEI 25000 -CQDs, PEI:CQDs = 10:1 (mass ratio), the right picture shows 0.05g PAM, 2mL PEI 25000 -CQDs, wherein PEI:CQDs=5:1 (mass ratio). DETAILED DESCRIPTION

[0029] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0030] The first aspect of the present invention provides a method for preparing a PEI-CQDs composite material, the method comprising:

[0031] (1) electrolyzing graphite in water to obtain carbon quantum dots;

[0032] (2) reacting carbon quantum dots and polyethyleneimine in the presence of an optional auxiliary agent to obtain a PEI-CQDs composite material.

[0033] Preferably, in step (1), the method for preparing carbon quantum dots comprises: using graphite rods as anode and cathode, using a direct current power supply to perform electrolysis in water to obtain an electrolyte, and purifying the electrolyte to obtain carbon quantum dots.

[0034] It should be understood that the graphite rod may be cleaned before electrolysis, for example, by using deionized water and anhydrous ethanol, etc., and the cleaning process may be accompanied by ultrasonic treatment. The size of the graphite rod may be conventional in the art and placed in a conventional manner for electrolysis. Preferably, the diameters of the cathode graphite rod and the anode grinding rod are independently 0.3-1 cm.

[0035] Preferably, the cathode graphite rod and the anode graphite rod are spaced 3-15 cm apart, preferably 5-10 cm apart.

[0036] Generally speaking, bubbles first appear in the anode graphite rod during the electrolysis process, and the solution slowly changes from colorless to yellow. As the electrolysis process proceeds, the anode graphite rod corrodes, and a dark yellow solution gradually appears until it turns completely black. In the present invention, the electrolysis time is not particularly limited and can be selected as needed, as long as carbon quantum dots can be obtained, for example, the time is 96-360 hours.

[0037] Preferably, the voltage is 5-50V, more preferably 10-40V.

[0038] The water may be deionized water or ultrapure water, etc. Preferably, the conductivity of the water is less than 10 μS / cm.

[0039] The inventors of the present invention have found that under the conditions of the preferred voltage, when electrolysis is carried out using water as the electrolyte, the proportion of carbonyl (carbon-oxygen double bond) in the oxygen-containing functional groups on the surface of carbon quantum dots can be further increased, so that the molar ratio of hydroxyl (carbon-oxygen single bond) to them can be further reduced.

[0040] The purification method can be a conventional method in the art, such as purification by means of solid-liquid separation and dialysis, specifically large particles can be removed by filtering, and then further purified by dialysis (dialysis can be performed for 2-4 days, and deionized water can be replaced once every 2-6 hours). The purified solution can be directly used in the preparation of composite materials, or it can be used after drying. The drying method can be a conventional method in the art, such as freeze drying.

[0041] When the CQDs are in powder form, they can be dispersed in deionized water before mixing with PEI to obtain a uniform and stably dispersed solution. For the description of the properties of the CQDs, please refer to the third aspect and will not be repeated here.

[0042] Preferably, in step (2), the weight ratio of polyethyleneimine to carbon quantum dots is 0.1-20:1, for example, it can be 0.1:1, 0.5:1, 1:1, 5:1, 10:1, 15:1, 20:1 and any range between any two values, more preferably 1-15:1.

[0043] Preferably, the molecular weight (Mw) of polyethyleneimine is 500-50000 g / mol, for example, 500, 600, 800, 1000, 1200, 1400, 1600, 1800, 2000, 3000, 4000, 50000 g / mol and any range between any two values, more preferably 600-20000 g / mol.

[0044] In one embodiment of the present invention, in step (2), the auxiliary agent comprises a cross-linking agent and / or an amino protecting agent.

[0045] Preferably, the cross-linking agent is 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl).

[0046] Preferably, the amino protecting agent is N-hydroxysuccinimide (NHS).

[0047] Preferably, the solvent is water. The solvent may include the solvent in the PEI solution and the CQDs solution.

[0048] Preferably, the weight ratio of carbon quantum dots, cross-linking agent and amino protective agent is 1:0.2-10 (for example, it can be 0.2, 0.5, 1, 2, 4, 6, 8, 10 and any range between any two values): 0.1-5 (for example, it can be 0.1, 0.5, 1, 2, 3, 4, 5 and any range between any two values), more preferably 1:0.5-5:0.2-2.

[0049] When adding the auxiliary agent, the order of adding the components is preferably to add the crosslinking agent and the amino protective agent to the CQDs solution, and then to add the PEI solution. The PEI solution may be added dropwise.

[0050] Preferably, the solvent is water. The solvent may include the solvent in the PEI solution and the CQDs solution and an additional solvent. The solvent may be water, such as deionized water or ultrapure water, etc. Preferably, the conductivity of the solvent is less than 10 μS / cm.

[0051] The amount of the solvent is not particularly limited as long as the reaction can proceed normally. Preferably, the ratio of carbon quantum dots to solvent is 1:10-1000, preferably 1:50-500, by weight.

[0052] The reaction may be accompanied by auxiliary measures such as stirring and / or ultrasound. The reaction temperature is not particularly limited and can be carried out at room temperature. The reaction time may be based on the completion of the reaction, for example, 12-36 hours.

[0053] After the reaction is completed, the material after the reaction can be purified. For example, the precipitate in the lower layer can be filtered out first, and then the upper solution can be dialyzed to remove uncrosslinked PEI. The dialyzed product can be dried (such as freeze-dried) to obtain the composite material.

[0054] In the present invention, the specific purification conditions may be conventional purification additives in the art, which will not be described in detail here.

[0055] The second aspect of the present invention provides a PEI-CQDs composite material prepared by the method described above.

[0056] For the properties of the composite material, please refer to the third aspect and will not be described in detail here.

[0057] The third aspect of the present invention provides a PEI-CQDs composite material, wherein the PEI-CQDs composite material comprises polyethyleneimine covalently modified with carbon quantum dots;

[0058] Among them, the molar ratio of hydroxyl to carbonyl in the oxygen-containing functional groups on the surface of carbon quantum dots is less than 1, for example, it can be 0.1, 0.2, 0.4, 0.6, 0.8, 0.9, 0.95 and any range between any two values, preferably 0.2-0.6.

[0059] Among them, the molar ratio of hydroxyl to carbonyl in the oxygen-containing functional groups on the surface of carbon quantum dots is determined by XPS of carbon quantum dots.

[0060] Preferably, the infrared spectrum of the PEI-CQDs composite material contains 1632-1638cm -1 (For example, it can be 1632, 1634, 1636, 1638cm -1 and any range between any two values) at C=C stretching vibration.

[0061] Preferably, the average particle size of the CQDs is 2-8 nm (eg, 2, 4, 6, 8 nm, and any range between any two values).

[0062] Preferably, the carbon quantum dots are obtained by electrolysis of graphite. The electrolysis method may be specifically described in the first aspect.

[0063] Preferably, by weight, in the PEI-CQDs composite material, the weight ratio of the part derived from polyethyleneimine to the carbon quantum dot part is 0.1-20:1, for example, it can be 0.1:1, 0.5:1, 1:1, 5:1, 10:1, 15:1, 20:1 and any range between any two values, more preferably 1-15:1.

[0064] Preferably, the molecular weight (Mw) of the PEI-CQDs composite material is 2000-100000 g / mol, for example, 2000, 5000, 10000, 20000, 40000, 60000, 80000, 100000 g / mol and any range between any two values.

[0065] Preferably, the molecular weight (Mw) derived from the polyethyleneimine (PEI) portion is 500-50000 g / mol, such as 500, 1000, 5000, 10000, 20000, 30000, 40000, 50000 g / mol and any range between any two values; more preferably 600-20000 g / mol.

[0066] The fourth aspect of the present invention provides the use of the PEI-CQDs composite material as described above in preparing a gel; preferably in preparing a polyacrylamide gel.

[0067] A fifth aspect of the present invention provides a method for preparing a gel, the method comprising: in the presence of the PEI-CQDs composite material as described above, contacting and reacting polyacrylamide with water to obtain a polyacrylamide gel.

[0068] Preferably, the reaction conditions include: a temperature of 60-120°C, more preferably 80-110°C.

[0069] The reaction time is not particularly limited as long as there is enough time to generate gel, for example, it can be more than 2 hours, preferably 10-50 hours.

[0070] Preferably, the weight ratio of polyacrylamide to PEI-CQDs is 100:2-20.

[0071] Preferably, the mass ratio of polyacrylamide to water is 0.1-15:100 by weight.

[0072] A sixth aspect of the present invention provides a gel prepared by the method described above.

[0073] The present invention will be described in detail below through examples.

[0074] Unless otherwise specified, all reagents and materials used were commercially available.

[0075] In the following examples, PEI with different molecular weights was purchased from Sinopharm Reagent Company, and its molecular weight corresponds to the subscript, such as PEI 1800 The molecular weight is 1800 g / mol.

[0076] The molar ratio of hydroxyl to carbonyl in the oxygen-containing functional groups on the surface of carbon quantum dots is determined by XPS.

[0077] The infrared spectrum of the PEI-CQDs composite material was measured by FT-IR.

[0078] Preparation Example 1

[0079] First, put a 15cm long and 0.6cm diameter graphite rod into a 500mL beaker, add deionized water and anhydrous ethanol respectively, ultrasonically clean each for 30min, and blow dry for use. Use tweezers to pick up the cleaned graphite rod, insert a graphite rod as a cathode into 1000mL deionized water, and place it parallel to another anode graphite rod, with a spacing of 5.5cm between the cathode graphite rod and the anode grinding rod. Use a 15V DC voltage for electrolysis for 240h until the solution turns completely black. After the electrolysis is completed, filter, remove large particles, concentrate by rotary evaporation, and dialyze for 3 days, where deionized water is replaced every 8h. Freeze-dry the dialyzed solution for 48h until it is completely dried into a powder, that is, CQDs are obtained and stored for use.

[0080] The transmission electron microscopy images of the CQDs are shown in Figure 1 As shown, it can be seen that the whole is spherical nanoparticles.

[0081] The XPS full spectrum of the CQDs is shown in Figure 2 As shown, it can be seen that it contains only carbon and oxygen. Figure 3 The XPS spectrum of C1s of CQDs is shown, and the molar ratio of hydroxyl to carbonyl in the oxygen-containing functional group is 0.5. It is determined that the average particle size of the CQDs is 3-5 nm.

[0082] Preparation Example 2

[0083] The operation was carried out in accordance with the method described in Preparation Example 1, except that the voltage was different, specifically 30V.

[0084] The shape of the prepared CQDs was basically the same as that prepared in Preparation Example 1, with a particle size of 4-7 nm and a molar ratio of hydroxyl to carbonyl in the oxygen-containing groups of 0.3.

[0085] Preparation Example 3

[0086] The operation was carried out according to the method described in Preparation Example 1, except that the solvent was different, specifically ethanol.

[0087] The shape of the prepared CQDs was substantially the same as that of the CQDs prepared in Preparation Example 1, with a particle size of 2 to 5 nm and a molar ratio of hydroxyl to carbonyl in the oxygen-containing groups of 0.8.

[0088] The inventors found during the experiment that when the molar ratio of hydroxyl and carbonyl in the CQDs prepared in Preparation Examples 1-3 is lower, it will be beneficial to promote the grafting of PEI and CQDs, thereby further improving the performance of PEI-CQDs in preparing gels.

[0089] Example 1

[0090] This example is used to illustrate PEI 600 -Preparation method of CQDs composite materials.

[0091] First, 0.2 g of the CQDs powder prepared in Example 1 was added to a 50 mL beaker containing 40 mL of deionized water using an electronic balance. Ultrasonic vibration was used to completely dissolve the CQDs powder in the deionized water to obtain a uniform, stably dispersed solution. Subsequently, 400 mg of EDC·HCl and 240 mg of NHS were weighed and added using an electronic balance, and then 2 g of PEI was added. 600; In this experiment, PEI in the form of aqueous solution was added dropwise to the CQDs aqueous solution at least three times. A magnetic particle was added to the beaker, and the reaction was stirred at room temperature for 24 hours to make it completely reacted, and then washed with deionized water 3-4 times, centrifuged to remove the lower precipitate, and the upper black solution was collected and dialyzed to remove the uncrosslinked PEI, and then freeze-dried for 24 hours to make it completely dry, to obtain PEI-CQDs (referred to as PEI 600 -CQDs) powder and store for future use.

[0092] About PEI 600 , CQDs and PEI-CQDs were subjected to infrared tests, and the test spectra were as follows Figure 4 As shown. Figure 4 It can be seen that the spectrum of CQDs contains a broad absorption peak followed by several overlapping peaks, most of which are due to the characteristic vibrations of chromophores of different functional groups in the internal structure of CQDs. Most of the bands in the spectrum of unmodified CQDs can be associated with the characteristic bonds of CH and C@C organic compounds, some of which come from the dehydration step. The peak is at 3419 cm -1 Corresponds to the stretching vibration of the OH bond; the second band is at 1500-2000cm -1 The stretching of C=O in CQDs includes 1624 cm -1 and 1700cm -1 The peak at 1444cm -1 It is due to the bond in the aliphatic CH3 group at the C point, 1239 cm -1 The peak at 1668 cm is the bending vibration of saturated CH. As can be seen from the figure, the spectrum of PEI-CQDs shows obvious absorption features of all PEI, with a peak at 1668 cm -1 This result confirms that PEI has successfully covalently modified CQDs. 600 -CQDs compared to PEI 600 Added 1635cm -1 The stretching vibration of C=C.

[0093] Example 2

[0094] This example is used to illustrate the preparation method of the PEI-CQDs composite material.

[0095] The operation was carried out according to the method described in Example 1, except that PEI with the same mass and different molecular weight was used instead of PEI 600, PEI-CQDs powder was obtained and stored for future use. The molecular weights of PEI were 1800 g / mol, 3000 g / mol, 10000 g / mol and 25000 g / mol, respectively. The obtained PEI-CQDs were respectively denoted as PEI 1800 -CQDs, PEI 3000 -CQDs, PEI 10000 -CQDs and PEI 25000 -CQDs, PEI 1800 -CQDs and PEI 10000 -Infrared spectra of CQDs are shown in Figure 5 As shown, C=C stretching vibration also exists, which confirms that PEI has successfully covalently modified CQDs.

[0096] The grafting effects of PEI with different molecular weights on CQDs were compared, and the results are shown in Table 1.

[0097] Table 1

[0098] type Experimental phenomenon After freeze drying <![CDATA[PEI 600 -CQDs]]> Centrifugation is basically non-stratified Viscous colloid, somewhat similar to the original PEI <![CDATA[PEI 1800 -CQDs]]> Only a small part of the stratification Colloidal black solid <![CDATA[PEI 3500 -CQDs]]> Only a small part of the stratification Colloidal black solid <![CDATA[PEI 10000- CQDs]]> Centrifugation is basically complete stratification Colloidal black solid <![CDATA[PEI 25000- CQDs]]> Centrifugation is basically complete stratification Colloidal black solid

[0099] Figure 6 and Figure 7 The distribution shows that PEI 1800 and PEI 1800 -GPC spectrum of CQDs. The sharper peak in the two figures is the solvent peak. The solvent is deionized water and the standard is polyethylene glycol. Because the test is related to the structure of the substance, molecular form, selected mobile phase, standard sample and other factors, the measured molecular weight will have a certain deviation. However, under the same conditions, the modified PEI-CQDs has an additional peak of 2895. It can be seen that the use of CQDs to modify PEI can increase the molecular weight of PEI.

[0100] Application Example 1

[0101] This application example is used to illustrate the preparation method of gel.

[0102] Polyacrylamide was mixed with distilled water, and then PEI or PEI-CQDs was added to react at 90°C for 12 hours, wherein the mass ratio of polyacrylamide to PEI or PEI-CQDs composite material was 100:8, and the mass ratio of polyacrylamide to water was 5:100. Among them, the sample without PEI or PEI-CQDs was recorded as blank control, and PEI was PEI 600 PEI 1800 PEI 10000 , PEI-CQDs composite materials are respectively the PEI-CQDs composite materials prepared in the above Example 1 (PEI 600 -CQDs, PEI 1800-CQDs, PEI 10000 -CQDs), and the gel time of different experimental groups was recorded. The results are shown in Table 2.

[0103] The gelation reaction process was observed by differential scanning calorimetry (DSC): DSC dynamic scanning showed two consecutive peaks. An absorption peak was observed at around 60 °C due to PAM hydrolysis, and another exotherm was observed at around 70 °C, which corresponds to the beginning of cross-linking of PAM with PEI or PEI-CQDs.

[0104] Table 2

[0105]

[0106]

[0107] As can be seen from Table 2 above, in the blank control group or when only low molecular weight PEI (PEI 600 ), no gel can be formed, but using PEI 600 -CQDs can form gel, and its gel time can be shorter than PEI 1800 From other experimental groups, it can also be seen that the gelation time can be significantly shortened after using PEI-CQDs composite materials.

[0108] Application Example 2

[0109] Polyacrylamide was mixed with distilled water, and then a certain amount of PEI-CQD composite material was added to observe its gelation at 70°C. The gelation time and gelation strength were determined by observing its gelation state using the gel code method. The gelation time was considered to be when the gel strength reached grade C. The SYDANSK gel code method was used to divide the plugging agent gel strength (abbreviated as GSC) into 10 grades according to the visual state, as shown in Table 3.

[0110] Table 3

[0111]

[0112]

[0113] The experimental groups included:

[0114] (1) Blank control: 0.5 g PAM was dissolved in 12 mL deionized water, placed in a sealed vial, and the gel state was observed at 70 °C.

[0115] (2) PEI group: 0.5 g PAM was dissolved in 10 mL deionized water, and 2 mL of 5% PEI (PEI 3000 PEI 10000PEI 25000 ), placed in a vial and sealed to obtain PAM / PEI 3000 , PAM / PEI 10000 , PAM / PEI 25000 , observe the gelation at 70℃.

[0116] (3) PEI-CQDs group: 0.5 g PAM was dissolved in 10 mL deionized water, and 2 mL of 5% PEI-CQDs (PEI 3000 -CQDs, PEI 1000 -CQDs, PEI 25000 -CQDs), placed in a vial and sealed to obtain PAM / CQDs / PEI 3000 , PAM / CQDs / PEI 10000 , PAM / CQDs / PEI 25000 , observe the gelation at 70℃.

[0117] The results of gelation time and gelation strength are shown in Table 4. Figure 8 PEI with different molecular weights (from left to right: PAM / PEI 3000 , PAM / PEI 10000 , PAM / PEI 25000 ) Gel image of the prepared PAM / PEI; Fig. 9 PEI with different molecular weights (from left to right: PAM / CQDs / PEI 3000 , PAM / CQDs / PEI 10000 , PAM / CQDs / PEI 25000 )Gel image of the prepared PAM / CQDs / PEI.

[0118] Table 4

[0119]

[0120]

[0121] From Table 4 and Fig. 9 It can be seen that the higher the PEI molecular weight, the shorter the gelation time and the greater the gel strength. Figure 8 By comparison, it can be seen that the gel strength is greater in the presence of CQDs. It can be inferred that CQDs may play the role of a crosslinking agent in the crosslinking system, accelerating the formation of a three-dimensional network structure and enhancing the system. This structure can contain water in the lattice structure to form a viscoelastic gel. It can be seen that grafting PEI with CQDs can effectively increase the molecular weight of PEI and improve the degree of branching of PEI, thereby improving its performance as a gel water plugging agent.

[0122] Fig.10 The gel images are obtained by using different amounts of CQDs. The left image is 0.05g PAM, 2mL PEI 25000 -CQDs, PEI:CQDs = 10:1 (mass ratio), the right picture shows 0.05g PAM, 2mL PEI 25000 -CQDs, where PEI:CQDs=5:1 (mass ratio). It can be seen that the mass ratio of CQDs to PEI affects the gel effect. Within a certain range, the more CQDs added, the better the gel effect.

[0123] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a PEI-CQDs composite material, characterized in that: The method includes: (1) electrolyzing graphite in water to obtain carbon quantum dots; (2) reacting carbon quantum dots and polyethyleneimine in the presence of an optional auxiliary agent to obtain a PEI-CQDs composite material.

2. The method according to claim 1, wherein: In step (1), the method for preparing carbon quantum dots comprises: using graphite rods as cathodes and anodes, using a direct current power supply to perform electrolysis in water to obtain an electrolyte, and purifying the electrolyte to obtain carbon quantum dots; Preferably, the cathode graphite rod and the anode grinding rod are spaced 3-15 cm apart, preferably 5-10 cm apart; Preferably, the voltage is 5-50V, more preferably 10-40V; Preferably, the conductivity of the water is less than 10 μS / cm; Preferably, in the oxygen-containing functional groups on the surface of the carbon quantum dots, the molar ratio of hydroxyl to carbonyl is less than 1, more preferably 0.2-0.

6.

3. The method according to claim 1 or 2, wherein: In step (2), the weight ratio of polyethyleneimine to carbon quantum dots is 0.1-20:1, preferably 1-15:1; and / or The molecular weight (Mw) of the polyethyleneimine is 500-50000 g / mol, preferably 600-20000 g / mol.

4. The method according to claim 1, wherein: In step (2), the auxiliary agent comprises a cross-linking agent and / or an amino protecting agent; and / or The reaction is carried out in an aqueous system; Preferably, the cross-linking agent is 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride; Preferably, the amino protecting agent is N-hydroxysuccinimide; Preferably, the weight ratio of carbon quantum dots, crosslinking agent and amino protective agent is 1:0.2-10:0.1-5, more preferably 1:0.5-5:0.2-2.

5. The PEI-CQDs composite material prepared by the method described in any one of claims 1 to 4.

6. A PEI-CQDs composite material, characterized in that: The PEI-CQDs composite material comprises polyethyleneimine covalently modified with carbon quantum dots; Among them, the molar ratio of hydroxyl to carbonyl in the oxygen-containing functional groups on the surface of the carbon quantum dots is less than 1.

7. The PEI-CQDs composite material according to claim 6, wherein The infrared spectrum of the PEI-CQDs composite material contains 1632-1638cm -1 The stretching vibration of C=C; and / or Wherein, the molar ratio of hydroxyl to carbonyl in the oxygen-containing functional groups on the surface of the carbon quantum dots is 0.2-0.6; and / or Wherein, in the PEI-CQDs composite material, the weight ratio of the part derived from polyethyleneimine to the carbon quantum dots part is 0.1-20:1, preferably 1-15:

1.

8. The PEI-CQDs composite material according to claim 6 or 7, wherein The molecular weight (Mw) of the portion derived from polyethyleneimine is 500-50000 g / mol, preferably 600-20000 g / mol.

9. Use of the PEI-CQDs composite material according to any one of claims 5 to 8 in preparing a gel; preferably in preparing a polyacrylamide gel.

10. A method for preparing a gel, characterized in that: The method comprises: in the presence of water, contacting and reacting the PEI-CQDs composite material according to any one of claims 5 to 8 with polyacrylamide to obtain a gel; Preferably, the reaction conditions include: a temperature of 60-120°C, more preferably 80-110°C; Preferably, the weight ratio of polyacrylamide to PEI-CQDs is 100:2-20; preferably, the weight ratio of polyacrylamide to water is 0.1-15:

100.

11. The gel prepared by the method according to claim 10.

Citation Information

Patent Citations

  • Preparation method for CQDs@PVP / PVDF composite dielectric film

    CN109082050A

  • Strontium titanate-carbon quantum dot composite material and preparation method and application thereof

    CN111036188A

  • Preparation method and application of fluorescent hydrogel dressing

    CN112358646A

  • Functionalized carbon quantum dot and preparation method thereof

    CN112521942A

  • Carbon material for detecting iron ions as well as synthesis method and application of carbon material

    CN114956048A